Synthesis of a phosphorus-based epoxy reactive flame retardant analog to diglycidyl ether of bisphenol A (DGEBA) and its behavior as a matrix in a carbon fiber composite. (November 2022) - Mukhtar, Mustafa; Klosterman, Donald; Benin, Vladimir; Morgan, Alexander
Highlights: P-DGEBA, a new DGEBA analog containing phosphorus, was successfully synthesized using two chemical synthesis techniques. P-DGEBA/DGEBA blend exhibited similar rheology to epoxy resin systems; formulation was achieved without additional heating. A technique for manufacturing high-quality carbon fabric composite laminates for flammability test has been developed. P-DGEBA has promise as a reactive flame retardant for epoxy since it maintains mechanical characteristics. Abstract: This paper describes the synthesis of a phosphorus-based flame retardant that is a chemical analog of diglycidyl ether of bisphenol A (DGEBA), as well as its incorporation as a matrix into carbon fiber laminates. Carbon fiber composites, if used for structural applications in mass transport vehicles (aircraft, trains), will require some aspects of improved fire performance to be used safely in those applications. The first phase of work involved the development of two separate synthesis routes to produce the flame retardant monomer, referred to as Phosphorus-DGEBA or simply P-DGEBA. The second step was to determine the viability of the compound's polymerization behavior through various experimental mixing formulations and curing conditions with an aliphatic amine curing agent. Differential scanning calorimetry (DSC) was used to evaluate the curing behavior of P-DGEBA when mixed with DGEBA and an aliphatic amine curing agent and dynamic mechanical analysis (DMA) was used to observe the glass transition temperature (Tg ) of the carbon fiber composites. Thermogravimetric analysis (TGA) was also used to investigate the thermal stability and thermal degradation behaviors of the P-DGEBA/DGEBA blends. The final step included the fabrication of composites and their flammability testing using a cone calorimeter. DMA testing for P-DGEBA measured a Tg that was 10 °C higher than a DGEBA based carbon fiber composite, and DSC studies found that the P-DGEBA / DGEBA blend polymerized well with the amine curing agent. The TGA, MCC, and cone calorimeter data yielded mixed results with TGA and MCC suggesting a more condensed phase / char formation flame retardant activity for P-DGEBA, while cone calorimeter suggested a more vapor phase flame retardant activity. Overall, the P-DGEBA shows some promise as a reactive FR for epoxy + carbon fiber composites, but more study is needed.